Meningkatkan Keputusan Pembelian dengan Kepercayaan, Celebrity Endorse dan Digital Marketing - Adnyani, Ni Made Widya; Pratiwi, Komang Ary (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The rapid development of the digital era is very helpful for companies to reach consumers more broadly and freely. Today's industrial digitalization needs to be utilized to maximize purchasing decisions for company products. This study examines the impact of trust, celebrity support, and also digital marketing in increasing purchasing decisions on E-commerce Shopee in Denpasar City. The size of the population is not known with certainty so that a representative sample is taken of 85 people. The method for analyzing the collected data uses multiple linear regression methods. From the analysis process that has been carried out, it is found that companies can increase purchasing decisions positively and also significantly by increasing trust, celebrity support, and digital marketing either partially or simultaneously. The suggestions put forward look at the results of research so that companies can continue to increase trust, celebrity support, and digital marketing so that purchasing decisions continue to increase on an ongoing basis